Degradation of benzo[a]pyrene by Pleurotus ostreatus PO‐3 in the presence of defined fungal and bacterial co‐cultures. (22nd November 2016) - Bhattacharya, Sourav; Das, Arijit; Palaniswamy, Muthusamy; Angayarkanni, Jayaraman
Abstract : Benzo[ a ]pyrene, a high molecular weight polycyclic aromatic hydrocarbon possesses carcinogenic, teratogenic, and mutagenic properties. The present study focuses on benzo[ a ]pyrene degradation by Pleurotus ostreatus PO‐3, characterization and identification of metabolites produced and the extent of degradation in the presence of axenic culture of P. ostreatus PO‐3 and defined co‐cultures of the basidiomycete with bacteria and non‐basidiomycete fungi. Thin‐layer chromatography revealed that P. ostreatus PO‐3 transformed benzo[ a ]pyrene to polar metabolites. Following degradation, appearance of numerous peaks in the mass spectrum indicated that benzo[ a ]pyrene degradation was a result of the metabolic activity of P. ostreatus PO‐3. A degradation product corresponding to the m/z 284.2 was detected which could possibly be B a P‐quinone, resulting from the oxidation of benzo[ a ]pyrene. Compared to the axenic culture of P. ostreatus PO‐3 (64.3%), co‐cultures of P. ostreatus PO‐3 and Penicillium chrysogenum MTCC 787 and P. ostreatus PO‐3 and Pseudomonas aeruginosa MTCC 1688 could degrade 86.1 and 75.1% of benzo[ a ]pyrene, respectively. Thus it could be inferred from the present investigation that the combined catabolic activities of P. ostreatus PO‐3 with bacteria and non‐basidiomycete fungi can produce synergistic effects to enhance B a P degradation. The increase in the generation of polar metabolites as degradation products from the recalcitrant parent compound advocates the potential application of P. ostreatus PO‐3 in benzo[ a ]pyrene bioremediation.